ANALISIS TOTAL FENOL, TANNIN, DAN KADAR SARI PRODUK HERBAL INSTAN BERBAHAN BAKU RIMPANG YANG BEREDAR DI PASAR SWALAYAN KOTA DENPASAR - Situmorang, Rani; Semadi Antara, Nyoman; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2014)
This research aimed to determine the amount of content of phenolic compounds, tannin, pollen levels and determine whatever there are differences between herbal products containing compounds that are produced by different companies on the instant herbal products made from raw rhizome circulating in Denpasar supermarket. This was an exploratory study, which is to determine the content of phenolic compounds, tannins, and juice content contained in the instant herbal products. The results showed that the instant herbal products that have the higest total levels of tannin white turmeric 0,12%, and the lowest tannin content was 0,02% ginger juice. Higest total phenol content was 80,06% white turmeric, and the lowest total phenol content was 26,00% red ginger. Instant herbal products that have the higest total pollen levels are ginger ginseng’s 2,07%, and each instant herbal products the lowest total pollen content was 1,18% turmeric acid . Each instant herbal products made from raw rhizome has a total phenol, total levels of tannin, and total levels of the different extracts.
Keywords: 12